Mechanisms of microRNA-mediated gene regulation in animal cells - Nilsen, Timothy W. (Trends in genetics, 2007)
MicroRNAs are a large family of regulatory molecules found in all multicellular organisms. Even though their functions are only beginning to be understood, it is evident that microRNAs have important roles in a wide range of biological processes, including developmental timing, growth control, and differentiation. Indeed, recent bioinformatic and experimental evidence suggests that a remarkably large proportion of genes (>30%) are subject to microRNA-mediated regulation. Although it is clear that microRNAs function by suppressing protein production from targeted mRNAs, there is, at present, no consensus about how such downregulation is accomplished. In this review, I describe the evidence that there are multiple mechanisms of microRNA-mediated repression and discuss the possible connections between these mechanisms.